Integrated transcriptomic and proteomic analysis reveals isolation and culture associated molecular changes in neonatal porcine pancreatic cell clusters - Chang-Yi Chen; Chen-Ling Chen; Chen-Wei Kao; Chen-Yi Chen; Wan-Wen Hung; Ching-Wen Chang; Jyuhn-Huarng Juang; Wan-Chun Li (Molecular Biology Reports, 2026)
Background While porcine Neonatal Pancreatic Cell Clusters (NPCCs) were potential alternative source of islets, their immaturity and heterogeneity make them inefficiently ameliorate hyperglycemia in rodents. Our previous work showed that NPCCs regress to a transitional-like state immediately after isolation and undergo dynamic transcriptional changes during short-term in vitro culture. The present study aimed to further delineate the molecular cues underlying these changes during porcine pancreatic tissue isolation and cultivation. Method Transcriptomic and proteomic analysis were performed to compare Neonatal Porcine Pancreata (NPP), freshly isolated NPCCs (NPCCs-0D) and 3-day in vitro cultured NPCCs (NPCCs-3D). Using an in-house analysis pipeline, molecular differences between groups were identified. Results NPCCs‑0D showed lower molecular abundance compared with NPP and NPCCs‑3D groups under the tested conditions. Gene Sets Enrichment Analysis (GSEA) revealed that pathways related to receptor signaling and cell–microenvironment interactions were enriched in NPP and NPCCs‑3D, highlighting the importance of external regulation in maintaining pancreatic tissue architecture. In contrast. organelle- and catalysis-associated gene sets were enriched in NPCCs‑0D, suggesting a transcriptionally active and adaptive state. Conclusion Collectively, these findings indicate that molecular differences among NPP, NPCCs-0D, and NPCCs-3D reflect changes in tissue organization, cellular composition, and adaptation to isolation and culture conditions, rather than a linear differentiation process.

Electrochemically synthesized potassium ferrate for diclofenac degradation: Performance, kinetics, and mechanistic insights - Chia-Hung Chen; Ching-Lung Chen; Hsin-Yu Chiang; Wu-Xing Chen; Amila Kasun Abeysinghe; Fang-Yu Liang; Chih-Chi Yang; Yen-Ping Peng (Journal of Water Process Engineering, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Rivers as microplastics gatekeepers: Linking terrestrial inputs to coastal sediment sinks and sources - Ting-Chang Hsu; Ahmad; Gwo-Ching Gong; Jheng-Jie Jiang; Hernando P. Bacosa; Hung-Chu Hsu; Ruei-Feng Shiu (Marine Pollution Bulletin, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Centrifuge modeling of tunnel uplift induced by liquefaction under successive seismic motions - Wen-Yi Hung; Jui-Ching Chou; Duc-Trung Tran; Chi-Tam Do (Soil Dynamics and Earthquake Engineering, 2026)

Consumer exposure risk to uropathogenic Escherichia coli from commonly consumed juice retailed in Taiwan: A quantitative microbial exposure assessment focused on sugarcane juice - Liu-Yean Goh; Ching-Wen Chang; L.-W. Antony Chen; Kuan-Hung Lu (Food Control, 2026)

AlgaePath 2.0: An updated database for revealing algal coding and non-coding gene interactions in metabolic pathways - Kuan-Chieh Tseng; Wen-Lin Wang; Yen-Lin Shen; Hung-Teng Wang; Ching-Ya Yuan; Chien-Wen Yang; Ching-Nen Nathan Chen; Wen-Chi Chang (Algal Research, 2026)

Aurone analog LYK01 exerts oxidative stress-dependent antiproliferation, G2/M arrest, apoptosis, and DNA damage of oral cancer cells involving MAPK modulation - Yan-Ning Chen; Chia-Hung Yen; Ching-Yu Yen; Ammad Ahmad Farooqi; Meng-Yang Chang; Tsu-Ming Chien; Jen-Yang Tang; Hsueh-Wei Chang (Molecular and Cellular Biochemistry, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Risk of skin cancer from hydrochlorothiazide and other diuretics across races: A global cohort study - Chaw-Ning Lee; Shih-Chieh Shao; Chao-Chun Yang; Jia-Horung Hung; Edward Chia-Cheng Lai; Ching-Chi Chi (Environmental Toxicology and Pharmacology, 2026)

How can severe rapid intensification of super-intense typhoons be revealed by the evolution of lower-stratospheric potential vorticity? - Thi-Chinh Nguyen; Ching-Yuang Huang; Hung-Chi Kuo (Atmospheric Research, 2026)

Combined Associations of Lead and Arsenic Species with Liver Dysfunction and Hepatic Fibrosis Among Young Adults in Taiwan - Kai-Wei Liao; Chih-Wen Wang; Wei-Lun Hung; Ya-Ling Chen; Yee-How Say; Yang-Ching Chen; Wei-Shan Chin (Exposure and Health, 2026)

Coupling fine-scale molecular approaches with hydrodynamic modeling to inform conservation management of the endangered and endemic fiddler crab Xeruca formosensis - Kun-Ching Hung; Hui-Chen Lin (Journal of Environmental Management, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Deep learning for extraneous material detection in a rice processing factory - Pei-Ting Chuang; Ming-Hung Cheng; Ching-Ho Chi; Hao-Hsiang Ku (Food Control, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Insertion of the PgRE1 retrotransposon into the promoter region of PgACS1, a system-2 ACC synthase gene, leads to variation in ripening ethylene production and the storability of different guava varieties - Margo Sulistio; You-Siang Liao; Hsin-Hung Yeh; Ching-Ping Lin; Hung-Yeh Hsieh; Chun-Ta Wu (Postharvest Biology and Technology, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Anchoring ultrafine CeO2 nanoparticles and loading TiO2 on reduced graphene oxide for photothermal catalytic elimination of NO and Hg0 - Ji-Ren Zheng; Chung-Shin Yuan; Ching-Ching Hsu; Huazhen Shen; Chung-Hsuang Hung (Journal of Environmental Chemical Engineering, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Preparation and integration of NIR-to-visible III-substituted In1-xGaxSe multilayers for high-efficiency solar cells and light-emitting devices - Yu-Hung Peng; Ming-Chueh Tsai; Luthviyah Choirotul Muhimmah; Yin-Chou Huang; Yen-Chang Su; Thalita Maysha Herninda; Ching-Hwa Ho (Chemical Engineering Journal, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Microplastics affect marine snow formation and sinking to the ocean's interior - Madeline Olivia; Wen-Huai Wu; An-Yi Tsai; Hung-Chu Hsu; Gwo-Ching Gong; Ruei-Feng Shiu (Water Research, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Quantitative microbial exposure assessment of uropathogenic Escherichia coli in ready-to-eat chicken: Consumer risk and mitigation strategies in Taiwan - Liu-Yean Goh; Ching-Wen Chang; L.-W. Antony Chen; Kuan-Hung Lu (Food Research International, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Antioral cancer effects of ginger derivative 3-HDM exert oxidative stress-associated apoptosis and DNA damage - Kuan-Liang Chen; Hsin-I Lu; Ching-Yu Yen; Chung-Yi Chen; Tsu-Ming Chien; Jiiang-Huei Jeng; Bing-Hung Chen; Hsueh-Wei Chang (Molecular Biology Reports, 2025)

Clinical validation of artificial intelligence-assisted karyotyping on peripheral blood in a cytogenetic diagnostic laboratory - Yujie Zhu; Matthew Hoi Kin Chau; Huilin Wang; Ning Song; Ran Wei; Kin Wah Suen; Anna Chi Sum Chan; Wan Ching Hung; Ye Cao; Zirui Dong; Tak Yeung Leung; Sau Wai Cheung; et al. (Human Genetics, 2025)
G-banded chromosome analysis, also known as G-banded karyotyping, remains a fundamental and irreplaceable diagnostic modality in clinical genetic testing. G-banded karyotypes provide whole genome visualization through chromosome banding patterns at the single-cell resolution for the diagnosis of chromosomal disorders. However, this method is labor-intensive and requires specialized expertise to manually analyze and karyotype metaphase spreads. In recent years, artificial intelligence (AI) algorithms have been utilized to automate karyotyping and assist with chromosome analysis. Despite this progress, there is a scarcity of studies evaluating the utility of artificial intelligence-assisted (AI-assisted) karyotyping analysis in cytogenetics diagnostic laboratories. This study highlights promising applications of AI-assisted karyotyping analysis in a cytogenetics diagnostic laboratory through a combination of a literature review, our data, and experience from a retrospective cohort study. This study also discusses important considerations of the use of AI-assisted karyotyping analysis in a cytogenetic diagnostic laboratory and outlines a two-stage framework for its implementation into clinical workflows. This approach aims to utilize the accuracy and efficiency of AI-assisted karyotyping analysis, potentially benefiting personalized patient care and contributing to advancements in the health system.

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Rosy-faced lovebirds are capable of associative symbol learning and inference-based quantity discrimination - Shengyu Wang; Kevin Ching Hei Lo; Verna Wing Ting Shiu; Christy Yuen Ching Hung; Emily Shui Kei Poon; Chris Newman; Christina D. Buesching; Simon Yung Wa Sin (Animal Behaviour, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Growth modeling of uropathogenic Escherichia coli in raw and cooked beef as a function of storage temperature for shelf life predictions - Liu-Yean Goh; Tzu-Ping Kao; Yi-Chun Pan; Ching-Wen Chang; Kuan-Hung Lu (International Journal of Food Microbiology, 2025)

Plasma-guided green synthesis of crystalline graphene quantum dots for broad-spectrum antiviral applications - Ren-Jie Weng; Li-Syuan Wu; Darwin Kurniawan; Ching-Tzu Chang; Ming-Han Tsai; Wei-Hung Chiang (Chemical Engineering Journal, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Molecular insights into the mechanism between the structural and mechanical properties of glycol chitosan methacrylate hydrogels - Kai-Hsiang Chang; Chia-Hung Wu; Zhen-Jie Gao; Yu-Chia Su; Ken-Tsung Wong; Yi-Cheun Yeh; Jiashing Yu; Chia-Ching Chou (Carbohydrate Polymers, 2025)

Effects of Cyclic Stretch on Chondrogenic Differentiation of Rat Adipose-Derived Stem Cells Cultured on Type-I Collagen Coated PDMS Membrane - Hung-Maan Lee; Hui-Ying Li; Yi-Ho Hsieh; Lassina Barro; Ching-Yi Cheng; Ming-Fa Hsieh (Journal of Medical and Biological Engineering, 2025)

Hydroxy stearic acids suppress pancreatic cancer stemness by targeting STAT3 signaling and mitochondrial proteome regulation - Ching-Feng Chiu; Yuan-Kai Qiu; Wei-Yu Kao; Yen-Hao Su; Wan-Yu Wang; Tung-Wei Hsu; Charupong Saengboonmee; Shao-Wen Hung; Olga G. Mountanea; Charikleia S. Batsika; George Kokotos; Shih-Yi Huang (Food Bioscience, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Dynamic vertical land motion driven by climate and humans in the metropolitan Taipei Basin - Pei-Chin Wu; Meng (Matt) Wei; Jyr-Ching Hu; Steven D'Hondt; Hsin Tung; Shao-Hung Lin; Christopher J. Russoniello (Remote Sensing Applications: Society and Environment, 2025)

Effects of humidity on photocatalytic oxidation of elemental mercury by rGO-modified CeO2/TiO2: Kinetic analysis and experimental exploration - Ji-Ren Zheng; Chung-Shin Yuan; Ting-Yu Chen; Ching-Ching Hsu; Chung-Hsuang Hung; Huazhen Shen (Journal of Environmental Chemical Engineering, 2025)

Association Between Urinary Paraben Concentrations and Early Renal Impairment in Young Adults in Taiwan - Wei-Shan Chin; Yung-Ning Chuang; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Ho-Ching Kao; Man-Ping Luo; Chia-Huang Chang; Kai-Wei Liao (Exposure and Health, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Challenges and limitations of applying the flux variance similarity (FVS) method to partition evapotranspiration in a montane cloud forest - Ching-Hung Shih; Ray G. Anderson; Todd. H. Skaggs; Jehn-Yih Juang; Yi-Ying Chen; Yi-Shin Jang; Rong-Yu Gu; Cho-Ying Huang; Min-Hui Lo (Agricultural and Forest Meteorology, 2025)

Modeling the growth and dynamics of uropathogenic Escherichia coli in sugarcane juice for shelf life predictions - Liu-Yean Goh; Ching-Wen Chang; Kuan-Hung Lu (Food Research International, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Rapid and noninvasive estimation of human arsenic exposure based on 4-photo-set of the hand and foot photos through artificial intelligence - Benny Wei-Yun Hsu; Wei-Wen Hsiao; Ching-Yi Liu; Vincent S. Tseng; Chih-Hung Lee (Journal of Hazardous Materials, 2024)

The influence of exposure to inorganic arsenic and other arsenic species on early renal impairment among young adults in Taiwan - Wei-Shan Chin; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Yun-Peng Lo; Kai-Wei Liao (Environmental Pollution, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Enhanced removal of sulfamethoxazole via adsorption and photodegradation using biochar-modified iodine-doped TiO2 photocatalysts under simulated sunlight - Yung-Dun Dai; Jia-Hou Lin; Chung-Hsuang Hung; Ching Yuan (Process Safety and Environmental Protection, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

Modelling the distribution of fish habitat type and habitat diversity in natural rivers - Hsuan-Ju Hung; Wei-Cheng Lo; Ching-Nuo Chen; Chih-Heng Tsai (Journal for Nature Conservation, 2024)

Cardenolide glycosides sensitize gefitinib-induced apoptosis in non-small cell lung cancer: inhibition of Na+/K+-ATPase serving as a switch-on mechanism - Chi-Min Du; Wohn-Jenn Leu; Yi-Huei Jiang; She-Hung Chan; Ih-Sheng Chen; Hsun-Shuo Chang; Lih-Ching Hsu; Jui-Ling Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Nutrient sources, phytoplankton blooms, and hypoxia along the Chinese coast in the East China Sea: Insight from summer 2014 - Chung-Chi Chen; Wen-Chen Chou; Chin-Chang Hung; Gwo-Ching Gong (Marine Pollution Bulletin, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Pioneering molecularly-level Fe sites immobilized on graphene quantum dots as a key activity descriptor in achieving highly efficient oxygen evolution reaction - Mia Rinawati; Ling-Yu Chang; Chia-Yu Chang; Ching-Cheng Chang; Darwin Kurniawan; Wei-Hung Chiang; Wei-Nien Su; Brian Yuliarto; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2024)

Enhancing methane formation in carbon dioxide hydrogenation on nickel clusters with zirconium additives: Exploring active sites, reaction pathways, and catalytic mechanisms - Ching-Shiun Chen; Tse-Ching Chen; Jia Huang Wu; Hung-Chi Wu; Chia-Min Yang; Tsung-Cheng Yang; Chih-Wen Pao (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

Economic strategies for efficient use of natural resources: The impact of carbon taxation and fiscal policy - Hui-Ching Cheng; Ming-Hung Shu; Jui-Chan Huang (Resources Policy, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Bioremediation of trichloroethylene-contaminated groundwater using green carbon-releasing substrate with pH control capability - Hsin-Chia Lee; Ssu-Ching Chen; Yih-Terng Sheu; Chao-Ling Yao; Kai-Hung Lo; Chih-Ming Kao (Environmental Pollution, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

An innovative permeable reactive bio-barrier to remediate trichloroethene-contaminated groundwater: A field study - Che-Wei Lu; Kai-Hung Lo; Sun-Chong Wang; Chih-Ming Kao; Ssu-Ching Chen (Science of The Total Environment, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

Trends in chitosan-based films and coatings: A systematic review of the incorporated biopreservatives, biological properties, and nanotechnology applications in meat preservation - Matthew Heras; Chia-Chi Huang; Ching-Wen Chang; Kuan-Hung Lu (Food Packaging and Shelf Life, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Probing the hair detectability of prohibited substances in sports: an in vivo-in silico-clinical approach and analytical implications compared with plasma, urine, and faeces - Shao-Hsin Hung; Hung-Lin Kan; Chun-Wei Tung; Yi-Ching Lin; Ting-Ting Chen; Ciao Tian; William Chih-Wei Chang (Archives of Toxicology, 2024)
Hair analysis is a crucial method in forensic toxicology with potential applications in revealing doping histories in sports. Despite its widespread use, knowledge about detectable substances in hair is limited. This study systematically assessed the detectability of prohibited substances in sports using a multifaceted approach. Initially, an animal model received a subset of 17 model drugs to compare dose dependencies and detection windows across different matrices. Subsequently, hair incorporation data from the animal experiment were extrapolated to all substances on the World Anti-Doping Agency’s List through in-silico prediction. The detectability of substances in hair was further validated in a proof-of-concept human study involving the consumption of diuretics and masking agents. Semi-quantitative analysis of substances in specimens was performed using ultra-performance liquid chromatography–tandem mass spectrometry. Results showed plasma had optimal dose dependencies with limited detection windows, while urine, faeces, and hair exhibited a reasonable relationship with the administered dose. Notably, hair displayed the highest detection probability (14 out of 17) for compounds, including anabolic agents, hormones, and diuretics, with beta-2 agonists undetected. Diuretics such as furosemide, canrenone, and hydrochlorothiazide showed the highest hair incorporation. Authentic human hair confirmed diuretic detectability, and their use duration was determined via segmental analysis. Noteworthy is the first-time reporting of canrenone in human hair. Anabolic agents were expected in hair, whereas undetectable compounds, such as peptide hormones and beta-2 agonists, were likely due to large molecular mass or high polarity. This study enhances understanding of hair analysis in doping investigations, providing insights into substance detectability.

Fluorinated photoreduced graphene oxide with semi-ionic C–F bonds: An effective carbon based photocatalyst for the removal of volatile organic compounds - Xin Hong Tai; Wei-Song Hung; Thomas Chung Kuang Yang; Chin Wei Lai; Kian Mun Lee; Chia-Yun Chen; Joon Ching Juan (Chemosphere, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)
Exposure of reproductive-age women to toxic trace elements warrants attention because of their negative effects. This study aimed to investigate the levels of arsenic (As), cadmium (Cd), mercury (Hg), chromium (Cr), and lead (Pb) in the blood of 837 Taiwanese childbearing-age women and establish the correlation between their dietary pattern and heavy metal concentration. The concentrations of Cd and Pb were significantly higher in nonpregnant women than in pregnant women (Cd: 2.41 µg/L vs. 2.12 µg/L; Pb: 0.83 µg/dL vs. 0.73 µg/dL), whereas the concentration of Cr was significantly lower in nonpregnant women than in pregnant women (Cr: 0.98 µg/L vs. 1.05 µg/L). Otherwise, no significant differences in As (9.02 µg/L vs. 9.51 µg/L) and Hg (3.71 µg/L vs. 3.79 µg/L) were found between the nonpregnant and pregnant women. Overall, the blood metal concentrations of Cd and Hg showed a decreasing trend in the different pregnancy stages. The levels of As and Hg were highly correlated with seafood intake. Finally, lifestyle habits, such as burning incense usage and Chinese herb intake may contribute to metal accumulation in maternal or reproductive-age women. Preventive risk communication and educational strategies should be applied to these subgroups in view of food safety and public health concern. Graphical Abstract

Consumption of the nonnutritive sweetener acesulfame potassium increases central precocious puberty risk - Hung-Tsung Wu; Chi-Chen Chiang; Chung-Teng Wang; Yue-Hwa Chen; Shih-Yuan Hsu; Yang-Ching Chen (Journal of Hazardous Materials, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Effect of sodium promoters on Ni/Al2O3 catalyst for CO2 hydrogenation: The carbon fixation as carbon nanofiber and reverse-water gas reactions - Ching-Shiun Chen; Tse-Ching Chen; Hung-Chi Wu; Jia-Huang Wu; Chih-Wen Pao (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Pinostrobin modulates FOXO3 expression, nuclear localization, and exerts antileukemic effects in AML cells and zebrafish xenografts - Pei-Yi Chen; Ching-Yen Lin; Chia-Ling Wu; Pei Ying Keak; Je-Wen Liou; Wan-Yun Gao; Liang-In Lin; Jui-Hung Yen (Chemico-Biological Interactions, 2023)

Interaction between driftwood deposition patterns and debris flow fan development - Yen-Yu Chiu; Jia-Yen Wu; Hung-En Chen; Ching-Ying Tsou; Su-Chin Chen (Landslides, 2023)

Microplastics in the soil environment: Focusing on the sources, its transformation and change in morphology - Junyu Zhu; Guowen Dong; Fu Feng; Jing Ye; Ching-Hua Liao; Chih-Hung Wu; Sheng-Chung Chen (Science of The Total Environment, 2023)

Evaluating criteria weights of street tree selection between residents and experts - Ching-Wen Wang; Hung-Ming Tu (Landscape and Ecological Engineering, 2023)

The use of immobilised bacteria cross-linked within magnetic alginate beads enhances the treatment of benzophenone-type UV filter chemicals by the SBR system - Sai Hung Lau; Ching-Lun Su; Ting-Yu Yu; YuYing Zhong; XinYuan Xu; Wann-Neng Jane; Yi-Tang Chang (Chemosphere, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Suspended particulate matter-bound per- and polyfluoroalkyl substances (PFASs) in a river-coastal system: Possible correlation with transparent exopolymer particles. - Ruei-Feng Shiu; Hui-Ju Lee; Hung-Te Hsu; Gwo-Ching Gong (Marine Pollution Bulletin, 2023)

A new species of Memnoniella (Hypocreales, Stachybotryaceae), Memnoniella pseudodichroa, from the ancient subtropical giant fern Angiopteris lygodiifolia (Marattiaceae) in Taiwan - Yu-Wei Yeh; Ching-Ming Hsieh; Yu-Hung Yeh; Yao-Moan Huang; Roland Kirschner (Plant Systematics and Evolution, 2023)

Enhancing the mechanical and hydromechanical behaviors of mudstone soils using sugarcane press mud - Febi Satria Gumanta; Soheil Ghadr; Chieh-Sheng Chen; Chih-Hsuan Liu; Ching Hung; Arya Assadi-Langroudi (Transportation Geotechnics, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

NOx removal and copper recovery from the leaching process for waste printed circuit boards: performance evaluation and potential environmental impact assessment - Tse-Lun Chen; Yen-Syun Chen; Pen-Chi Chiang; Yi-Hung Chen; Ching-Hsiang Hsu (Environmental Science and Pollution Research, 2023)

Biological treatment of benzophenone-type UV filter wastewater in a sequencing batch reactor (SBR) - Ching-Lun Su; Sai Hung Lau; Hsiang-Yuan Yeh; Yi-Tang Chang (International Biodeterioration & Biodegradation, 2023)

Thermal inactivation kinetics of uropathogenic Escherichia coli in sous-vide processed chicken breast - Yun-Jung Lee; Yi-Chun Pan; Ching-Wen Chang; Kuan-Hung Lu (Food Research International, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Adopting abundant seawater as green chemical activators for preparing high surface area biochar - TsingHai Wang; Yu-Ching Lin; Ci-Jing Hung; Yasi Liao; Ruo-Xin Xu (Bioresource Technology Reports, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

Concentrations and Characteristics of Polybrominated Diphenyl Ethers (PBDEs) in Marine Zooplankton from the Gaoping Waters of Southwestern Taiwan - Hung-Yen Hsieh; Kuang-Ching Huang; Jing-O Cheng; Fung-Chi Ko; Pei-Jie Meng (Journal of Marine Science and Engineering, 2022)
Bioaccumulation by zooplankton is the outset for persistent organic pollutants that enter the marine food chain. Owing to a full spectrum of anthropogenic activities, the Gaoping waters of southwestern Taiwan are exposed to large quantities of polybrominated diphenyl ethers (PBDEs). However, information on these contaminants in zooplankton in this study area is lacking. In this study, we analyzed 19 PBDE congeners concentrations in 36 zooplankton samples from the Gaoping waters. A high variation in the total PBDE concentrations in zooplankton (from not detected to 1415 ng g−1 dry weight) was found, with the highest PBDE levels being recorded near the entrance of the Kaohsiung Harbor (KH). Significantly higher levels were noted for the KH transect than for the Gaoping River estuary (GR) and Fengshan Township (FS) transects, indicating that PBDE inputs originate from the ocean sewage outfalls. BDE-15 (43%) and BDE-209 (16%) were the predominant PBDE congeners in the zooplankton. Our results suggest that anthropogenic activities might predominantly contribute to significantly high PBDE concentrations. The traditional food web may easily transport these higher levels of PBDEs in zooplankton to higher trophic levels of marine organisms, since the Gaoping waters serve as essential nursery and spawning grounds for invertebrates and fishes.

Efficacy of methylphenidate for the treatment of apathy in patients with Alzheimer’s disease: a systematic review and meta-analysis of randomized controlled studies - Chia-Wei Lee; Jui-Yi Chen; Ching-Chung Ko; Min-Hsiang Chuang; Wen-Wen Tsai; Cheuk-Kwan Sun; Kuo-Chuan Hung (Psychopharmacology, 2022)

Mechanical behavior of sands reinforced with shredded face masks - Soheil Ghadr; Chieh-Sheng Chen; Chih-hsuan Liu; Ching Hung (Bulletin of Engineering Geology and the Environment, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chung-Chi Chen; Dong S. Ko; Gwo-Ching Gong; Chun-Chi Lien; Wen-Chen Chou; Hung-Jen Lee; Fuh-Kwo Shiah; Yu-Sin Wita Huang (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occur in the summer, and well-mixed water typically reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on hypoxia and, therefore, on the ecosystem in the ECS is not known. This study demonstrates both positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, the spatial extent of hypoxic water increases with a lower pH but waters with high regenerated nutrients and fugacity of CO 2 ( f CO 2 ), which are normally confined to the near-bottom, are found just up to 5–10 m below the surface. This upwelled high nutrient water can enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km 2 . During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a , and slightly undersaturated dissolved oxygen but saturated f CO 2 , alongside a normal pH. This event may have served as an important pathway from the ocean to the atmosphere for the regenerated CO 2 . It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Scaling effects of a eutrophic river plume on organic carbon consumption - Chung‐Chi Chen; Gwo‐Ching Gong; Kuo‐Ping Chiang; Fuh‐Kwo Shiah; Chih‐Ching Chung; Chin‐Chang Hung (Limnology and Oceanography, 2021)
The amount of fluvial input has important impacts on shelf regions. To understand how the magnitude of fluvial discharge affects plume ecosystems, particularly organic carbon consumption, data over 10 consecutive summers (2003–2012) were examined in the Changjiang River plume of the East China Sea. The area of the Changjiang River plume ranged from approximately 4.90 × 10 3 km 2 to 94.83 × 10 3 km 2 and varied in proportion to the freshwater discharge rate. Plankton community respiration was at the medium to high end of the values reported for coastal regions. Total organic carbon consumption over the Changjiang River plume was positively correlated with the Changjiang freshwater discharge. This scaling relationship might be associated with river flows delivering allochthonous organic carbon and dissolved inorganic nutrients into the East China Sea. However, plankton community respiration (per m 3 basis) decreased as the area of the Changjiang River plume increased; this rate appeared to have been influenced by particulate organic carbon (POC) levels and/or total plankton biomass. Even though POC was dominated by phytoplankton biomass allometrically, bacteria contributed more to plankton community respiration, possibly signifying that these bacteria were more reliant on plankton‐derived organic matter. Even with high phytoplankton biomass and primary productivity, this plume ecosystem was heterotrophic, albeit close to a state of carbon balance. To support high organic carbon consumption, in addition to allochthonous sources from fluvial runoff, a large amount of organic matter might have been autochthonous and derived from plankton in the Changjiang River plume.

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Short‐term homeostatic regulation of blood/interstitial fluid Ca 2+ concentration by the scales of anadromous sea trout Salmo trutta L. during smoltification and migration - Leanna Jamieson; Angel Waters; Kaitlyn E. Ho; Harvey Y. S. Chan; Jacky T. Hung; Sarah E. Webb; Ching Man Chan; Alan M. Shipley; John G. Williamson; Jon Beer; Chevonne Angus; Andrew L. Miller (Journal of Fish Biology, 2021)
The elasmoid scales of anadromous sea trout Salmo trutta L. represent a significant internal reservoir of Ca 2+ . Although more is known about long‐term remodelling of scales in response to calciotropic challenges encountered during smoltification and migration, very little is known about the contribution made by scales to the short‐term, minute‐to‐minute regulation of Ca 2+ homeostasis in the extracellular fluid (ECF) during these phases of the life cycle. This gap in the knowledge is partly due to the technical challenges involved in measuring small Ca 2+ fluxes around the scales of live fish in real time. Here, this study describes exfoliating, mounting and culturing scales and their resident cells from parr, smolt and adult sea trout from a freshwater environment, as well as from adult sea trout caught in sea or brackish water. All the scales were then examined using an extracellular, non‐invasive, surface‐scanning Ca 2+ ‐sensitive microelectrode. The authors quantified the Ca 2+ fluxes, in the absence of any systemic or local regulators, into and out of scales on both the episquamal and hyposquamal sides under different extracellular calcemic challenges set to mimic a variety of ECF‐Ca 2+ concentrations. Scales from the life‐cycle stages as well as from adult fish taken from sea, brackish or fresh water all showed a consistent efflux or influx of Ca 2+ under hypo‐ or hypercalcemic conditions, respectively. What were considered to be isocalcemic conditions resulted in minimal flux of Ca 2+ in either direction, or in the case of adult scales, a consistent but small influx. Indeed, adult scales appeared to display the largest flux densities in either direction. These new data extend the current understanding of the role played by fish scales in the short‐term, minute‐to‐minute homeostatic regulation of ECF‐Ca 2+ concentration, and are similar to those recently reported from zebrafish Danio rerio scales. This suggests that this short‐term regulatory response might be a common feature of teleost scales.

Combination of “generalized Trotter operator splitting” and “quadratic adaptive algorithm” method for tradeoff among speedup, stability, and accuracy in the Markov chain model of sodium ion channels in the ventricular cell model - Xing-Ji Chen; Ching-Hsing Luo; Min-Hung Chen (Medical & Biological Engineering & Computing, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Short-Term Variability of Biological Production and CO2 System Around Dongsha Atoll of the Northern South China Sea: Impact of Topography-Flow Interaction - Jen-Hua Tai; Wen-Chen Chou; Chin-Chang Hung; Kuan-Chieh Wu; Ying-Hsuan Chen; Tzong-Yueh Chen; Gwo-Ching Gong; Fuh-Kwo Shiah; Chun Hoe Chow (Frontiers in Marine Science, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Genetic sequence changes related to the attenuation of avian infectious bronchitis virus strain TW2575/98 - Cheng-Ta Tsai; Hung-Yi Wu; Ching-Ho Wang (Virus Genes, 2020)

Dysregulations of mitochondrial quality control and autophagic flux at an early age lead to progression of sarcopenia in SAMP8 mice - Hung-Wen Liu; Yun-Ching Chang; Yin-Ching Chan; Shu-Hui Hu; Ming-Yi Liu; Sue-Joan Chang (Biogerontology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Posture Stability and Kinematics While Performing a 180° Turning Step in Elderly Individuals With and Without Vertebral Compression Fracture and in Middle-Aged Adults - Fang-Chuan Kuo; Yin-Yin Liao; Cheng-Hung Lee; Ben-Yi Liau; Ching-Cheng Pan (Journal of Medical and Biological Engineering, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Failure mechanism of a mudstone slope embedded with steep anti-dip layered sandstones: case of the 2016 Yanchao catastrophic landslide in Taiwan - Cheng-Han Lin; Ching Hung; Meng-Chia Weng; Ming-Lang Lin; Ryosuke Uzuoka (Landslides, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Combination of “quadratic adaptive algorithm” and “hybrid operator splitting” or uniformization algorithms for stability against acceleration in the Markov model of sodium ion channels in the ventricular cell model - Xing-Ji Chen; Ching-Hsing Luo; Min-Hung Chen; Xiang Zhou (Medical & Biological Engineering & Computing, 2019)

The Aso-Bridge coseismic landslide: a numerical investigation of failure and runout behavior using finite and discrete element methods - Ching Hung; Chih-Hsuan Liu; Guan-Wei Lin; Ben Leshchinsky (Bulletin of Engineering Geology and the Environment, 2019)

Stable isotope analysis reveals ontogenetic feeding shifts in Pacific blue marlin ( Makaira nigricans ) off eastern Taiwan - Ching‐Tsun Chang; Wei‐Chuan Chiang; Yun‐Chen Chang; Michael K. Musyl; Chi‐Lu Sun; Daniel J. Madigan; Aaron B. Carlisle; Hung‐Hung Hsu; Qi‐Xuan Chang; Nan‐Jay Su; Yuan‐Shing Ho; Chen‐Te Tseng (Journal of Fish Biology, 2019)
To gain a better understanding of the trophic ecology of Pacific blue marlin Makaira nigricans off eastern Taiwan, nitrogen and carbon stable isotopes (δ 15 N and δ 13 C) and Bayesian mixing models were used to explore trophic dynamics and potential ontogenetic feeding shifts across M. nigricans of different size classes. Makaira nigricans samples from east of Taiwan ( n = 213) and Palau ( n = 37), as well as their prey ( n = 70), were collected during 2012 and 2013. Results indicated increases in δ 15 N with size, with values of larger size classes (> 200 cm eye‐to‐fork length; L EF ) significantly higher than those L EF . Values of δ 13 C were negatively correlated with size. Makaira nigricans > 200 cm L EF had the highest estimated trophic position (4.44) and also exhibited ontogenetic changes in trophic position. Large M. nigricans fed more on dolphinfish Coryphaena hippurus and hairtail Trichiurus lepturus , while smaller M. nigricans consumed smaller forage fish ( e.g ., moonfish Mene maculata ) and cephalopods. These changes may relate to greater swimming speeds and vertical habitat use in larger M. nigricans , allowing capture and consumption of larger prey items at higher trophic positions. The high trophic level of M. nigricans east of Taiwan confirms its important role as an apex predator in marine food webs and how ecological role changes with size.

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Quantifying Phosphorus Sources and Sinks in the Gaoping River-Sea System in Southwestern Taiwan - Jia-Jang Hung; Yi-Ching Yeh (Estuaries and Coasts, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Evaluation of an enhanced FS method for finding the initiation time of earthquake-induced landslides - Guan-Wei Lin; Ching Hung; Huei-Sian Syu (Bulletin of Engineering Geology and the Environment, 2019)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Changes in Trace Elements During Early Stages of Chronic Kidney Disease in Type 2 Diabetic Patients - Ching-Chiang Lin; Ching-Tang Shih; Chien-Hung Lee; Yeou-Lih Huang (Biological Trace Element Research, 2018)

Identification of Ca2+ signaling components in neural stem/progenitor cells during differentiation into neurons and glia in intact and dissociated zebrafish neurospheres - Man Kit Tse; Ting Shing Hung; Ching Man Chan; Tiffany Wong; Mike Dorothea; Catherine Leclerc; Marc Moreau; Andrew L. Miller; Sarah E. Webb (Science China Life Sciences, 2018)

Analysis of the Aso-Bridge landslide during the 2016 Kumamoto earthquakes in Japan - Ching Hung; Guan-Wei Lin; Huei-Sian Syu; Chi-Wen Chen; Hsin-Yi Yen (Bulletin of Engineering Geology and the Environment, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Finite Element Analysis of Tongue Type Calcaneal Fracture with Open Reduction and Internal Fixation with Locking Plate - Ching-Hsuan Chen; Yu-Hsuan Huang; Chinghua Hung; Chen-Sheng Chen; Chao-Ching Chiang (Journal of Medical and Biological Engineering, 2018)

Application of RuO2/Ni foam electrodes for remediation of ibuprofen in soil matrix—the effect of electrokinetic parameters - Ching Yuan; Chung-Hsuang Hung; Tzu-Yuan Huang (Environmental Science and Pollution Research, 2018)

Assessing climate change adaptations for community-scale water resources using a low-frequency weather generator - Yuan-Hua Li; Ching-Pin Tung; Yuan-Hung Li; Pei-Yuan Chen (Paddy and Water Environment, 2018)

Biomechanical evaluation of reconstruction plates with locking, nonlocking, and hybrid screws configurations in calcaneal fracture: a finite element model study - Ching-Hsuan Chen; Chinghua Hung; Yu-Chun Hsu; Chen-Sheng Chen; Chao-Ching Chiang (Medical & Biological Engineering & Computing, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Identification of 3-MCPD esters to verify the adulteration of extra virgin olive oil - Wei-Ching Hung; Guan-Jhih Peng; Wen-Ju Tsai; Mei-Hua Chang; Chia-Ding Liao; Su-Hsiang Tseng; Ya-Min Kao; Der-Yuan Wang; Hwei-Fang Cheng (Food Additives & Contaminants Part B-Surveillance, 2017)

Alginate gel particles–A review of production techniques and physical properties - Su Hung Ching; Nidhi Bansal; Bhesh Bhandari (Critical Reviews in Food Science and Nutrition, 2017)

Differential MicroRNA Expression Profile of Human Embryonic Stem Cell-Derived Cardiac Lineage Cells - Yoon Young Kim; Harry Min; Hoon Kim; Young Min Choi; Hung Ching Liu; Seung-Yup Ku (Tissue Engineering and Regenerative Medicine, 2017)

Strain distribution, growth eccentricity, and tension wood distribution in the plagiotropic and orthotropic branches of Koelreuteria henryi Dummer - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Insulin Receptor Substrate-1 Activation Mediated p53 Downregulation Protects Against Hypoxic-Ischemia in the Neonatal Brain - Yi-Fang Tu; Si-Tse Jiang; Yen-Hung Chow; Chao-Ching Huang; Chien-Jung Ho; Ya-Ping Chou (Molecular Neurobiology, 2016)

The disintegrin, trimucrin, suppresses LPS-induced activation of phagocytes primarily through blockade of NF-κB and MAPK activation - Yu-Chun Hung; Chun-Chieh Hsu; Ching-Hu Chung; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Study of tension wood in the artificially inclined seedlings of Koelreuteria henryi Dummer and its biomechanical function of negative gravitropism - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2016)

Current temporal asymmetry and the role of tides: Nan-Wan Bay vs. the Gulf of Elat - Yosef Ashkenazy; Erick Fredj; Hezi Gildor; Gwo-Ching Gong; Hung-Jen Lee (Ocean Science, 2016)
Nan-Wan Bay in Taiwan and the Gulf of Elat in Israel are two different coastal environments, and as such, their currents are expected to have different statistical properties. While Nan-Wan Bay is shallow, has three open boundaries, and is directly connected to the open ocean, the Gulf of Elat is deep, semi-enclosed, and connected to the Red Sea via the Straits of Tiran. Surface currents have been continuously measured with fine temporal (less than or equal to 1 h) and spatial resolution (less than or equal to 1 km) for more than a year in both environments using coastal radars (CODARs) that cover a domain of roughly 10 × 10 km. These measurements show that the currents in Nan-Wan Bay are much stronger than those in the Gulf of Elat and that the mean current field in Nan-Wan Bay exhibits cyclonic circulation, which is stronger in the summer; in the Gulf of Elat, the mean current field is directed southward and is also stronger during the summer. We have compared the statistical properties of the current speeds in both environments and found that both exhibit large spatial and seasonal variations in the shape parameter of the Weibull distribution. However, we have found fundamental and significant differences when comparing the temporal asymmetry of the current speed (i.e., the ratio between the time during which the current speed increases and the total time). While the Nan-Wan Bay currents are significantly asymmetric, those of the Gulf of Elat are not. We then extracted the tidal component of the Nan-Wan Bay currents and found that it is strongly asymmetric, while the asymmetry of tidally filtered currents is much weaker. We thus conclude that the temporal asymmetry of the Nan-Wan Bay currents reported here is due to the strong tides in the region. We show that the asymmetry ratio in Nan-Wan Bay varies spatially and seasonally: (i) the currents increase rapidly and decay slowly in the northern part of the domain and vice versa in the southern part, and (ii) the asymmetry is stronger during summer.

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Identification of Microalgae by Laser Desorption/Ionization Mass Spectrometry Coupled with Multiple Nanomatrices - Lung-Hsiang Peng; Binesh Unnikrishnan; Chi-Yu Shih; Tung-Ming Hsiung; Jeng Chang; Pang-Hung Hsu; Tai-Chia Chiu; Chih-Ching Huang (Marine Biotechnology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Lipopolysaccharide-Binding Motif Derived Peptides Induce Cell Membrane Damages in Human Lung Cancer and Hepatoma Cell Lines - Hung-Hung Sung; Wann-Neng Jane; Wen-Yi Kao; Po-Ying Fu; Shih-Ching Ho; Chu-Wen Yang (International Journal of Peptide Research and Therapeutics, 2015)

Genetic variants of retinol-binding protein 4 in adolescents are associated with liver function and inflammatory markers but not with obesity and insulin resistance - CHIN-JUNG LIN; NAIN-FENG CHU; YI-JEN HUNG; DEE PEI; CHIEN-HSING LEE; FONE-CHING HSIAO; CHIEH-HUA LU; CHANG-HSUN HSIEH (Journal of Genetics, 2015)

Hydrolyzed 5-Azacytidine Enhances Differentiation of Rat Mesenchymal Stem Cells into Cardiomyocytes - Shwu Jen Chang; Yi-Jhen Wu; Shu Ching Tang; Hung-Yi Wang; Shyh Ming Kuo (Journal of Medical and Biological Engineering, 2015)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

CD200 in growing rat lungs: developmental expression and control by dexamethasone - Mang-Hung Tsai; Chin-Chen Chu; Tsui-Shan Wei; Mei-Miao Chiu; Chiu-Yun Chang; I-Hua Wei; Hsiung-Fei Chien; Hui-Min Chen; Ching-Hsiang Wu; Ya-Fen Jiang-Shieh (Cell and Tissue Research, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Application of Neural Networks and Optimization Model in Conjunctive Use of Surface Water and Groundwater - Ching-Wen Chen; Chih-Chiang Wei; Hung-Jen Liu; Nien-Sheng Hsu (Water Resources Management, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Analytical Expression for Vertical Stress within an Inclined Mine Stope with Non-parallel Walls - Ching Hung Ting; Nagaratnam Sivakugan; Wayne Read; Sanjay Kumar Shukla (Geotechnical and Geological Engineering, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

α-Mangostin induces mitochondrial dependent apoptosis in human hepatoma SK-Hep-1 cells through inhibition of p38 MAPK pathway - Shu-Ching Hsieh; Min-Hsien Huang; Chun-Wen Cheng; Jyun-Hao Hung; Shun-Fa Yang; Yi-Hsien Hsieh (Apoptosis, 2013)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Skin Permeation of Small-Molecule Drugs, Macromolecules, and Nanoparticles Mediated by a Fractional Carbon Dioxide Laser: The Role of Hair Follicles - Woan-Ruoh Lee; Shing-Chuan Shen; Saleh A. Al-Suwayeh; Hung-Hsu Yang; Yi-Ching Li; Jia-You Fang (Pharmaceutical Research, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

Copper accumulation, translocation, and toxic effects in grapevine cuttings - Kai-Wei Juang; Yung-I Lee; Hung-Yu Lai; Chiung-Huei Wang; Bo-Ching Chen (Environmental Science and Pollution Research, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Biogeochemical Responses in the Southern East China Sea After Typhoons - Chin-Chang Hung; Gwo-Ching Gong (Oceanography, 2011)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Prostaglandin I2 analogues suppress TNF-α expression in human monocytes via mitogen-activated protein kinase pathway - Wei-Li Wang; Chang-Hung Kuo; Yu-Te Chu; Ching-Hua Huang; Ka-Pan Lam; Shau-Ku Huang; Yuh-Jyh Jong; Yu-Ting Kuo; Chih-Hsing Hung (Inflammation Research, 2011)

Coupling bioaccumulation and phytotoxicity to predict copper removal by switchgrass grown hydroponically - Kai-Wei Juang; Hung-Yu Lai; Bo-Ching Chen (Ecotoxicology, 2011)

Characterization of Expressed Sequence Tags from Flower Buds of Alpine Lilium formosanum using a Subtractive cDNA Library - Wei-Kuang Wang; Chia-Chin Liu; Tzen-Yuh Chiang; Ming-Tse Chen; Chang-Hung Chou; Ching-Hui Yeh (Plant Molecular Biology Reporter, 2011)

Using chemical fractionation to evaluate the phytoextraction of cadmium by switchgrass from Cd-contaminated soils - Bo-Ching Chen; Hung-Yu Lai; Dar-Yuan Lee; Kai-Wei Juang (Ecotoxicology, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Calculation of bed load based on the measured data of suspended load - Chang-Tai Tsai; Chih-Heng Tsai; Chun-Hung Weng; Jinn-Jong Bair; Ching-Nuo Chen (Paddy and Water Environment, 2010)

Differential distributions of CSE1L/CAS and E-cadherin in the polarized and non-polarized epithelial glands of neoplastic colorectal epithelium - Wu-Ching Uen; Cheng-Jeng Tai; Shing-Chuan Shen; Woan-Ruoh Lee; Tang-Yi Tsao; Win-Ping Deng; Hung-Yi Chiou; Chung-Huei Hsu; Cheng-I Hsieh; Ching-Fong Liao; Ming-Chung Jiang (Journal of Molecular Histology, 2010)

Cloning, expression and physiological analysis of broccoli catalase gene and Chinese cabbage ascorbate peroxidase gene under heat stress - Kuan-Hung Lin; Ho-Chang Huang; Ching-Yun Lin (Plant Cell Reports, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Lycopene binding compromised PDGF-AA/-AB signaling and migration in smooth muscle cells and fibroblasts: prediction of the possible lycopene binding site within PDGF - Ching-Pei Chen; Chi-Feng Hung; Shao-Chen Lee; Huey-Ming Lo; Pi-Hui Wu; Wen-Bin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Influence of accuracy constraints on bimanual coordination during a goal-directed task in children with hemiplegic cerebral palsy - Ya-Ching Hung; Jeanne Charles; Andrew M. Gordon (Experimental Brain Research, 2010)

Characteristics of exhaust gas, liquid products, and residues of printed circuit boards using the pyrolysis process - Hung-Lung Chiang; Cho-Ching Lo; Sen-Yi Ma (Environmental Science and Pollution Research, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of chronic 4-n-nonylphenol treatment on aortic vasoconstriction and vasorelaxation in rats - Chi-Ying Hsieh; Chang-Ling Miaw; Chien-Cheng Hsieh; Hui-Ching Tseng; Yuan-Han Yang; Chia-Hung Yen (Archives of Toxicology, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jen Liu (Apoptosis, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jeng Liu (Apoptosis, 2009)

Detection of race 1 strains of Ralstonia solanacearum in field samples in Taiwan using a BIO-PCR method - Chih-Hung Lin; Shih-Tien Hsu; Kuo-Ching Tzeng; Jaw-Fen Wang (European Journal of Plant Pathology, 2009)

Learning a multi-joint throwing task: a morphometric analysis of skill development - Ya-Ching Hung; T. R. Kaminski; Julie Fineman; Jane Monroe; A. M. Gentile (Experimental Brain Research, 2008)

Contaminant Concentrations and Histopathological Effects in Sacramento Splittail (Pogonichthys macrolepidotus) - Ben K. Greenfield; Swee J. Teh; John R. M. Ross; Jennifer Hunt; GuoHua Zhang; Jay A. Davis; Gary Ichikawa; David Crane; Silas S. O. Hung; DongFang Deng; Foo-Ching Teh; Peter G. Green (Archives of Environmental Contamination and Toxicology, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Interleukin-1 receptor antagonist restores homeostatic function and limits multiorgan damage in heatstroke - Kun-Hung Shen; Chen-Kuei Chang; Mao-Tsun Lin; Ching-Ping Chang (European Journal of Applied Physiology, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Summer distribution and geochemical composition of suspended-particulate matter in the east china sea - Jia-Jang Hung; Chia-Lin Chan; Gong-Ching Gong (Journal of Oceanography, 2007)

Location and Characterization of Emission Sources for Airborne Volatile Organic Compounds Inside a Refinery in Taiwan - Ching-Liang Chen; Chi-Min Shu; Hung-Yuan Fang (Environmental Monitoring and Assessment, 2006)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Alpha-smooth muscle actin expression and structure integrity in chondrogenesis of human mesenchymal stem cells - Shih-Chieh Hung; Pei-Yin Kuo; Ching-Fang Chang; Tain-Hsiung Chen; Larry Low-Tone Ho (Cell and Tissue Research, 2006)

Corals have already evolved the vertebrate-type hormone system in the sexual reproduction - Wen-Hung Twan; Hua-Fang Wu; Jiang-Shiou Hwang; Yan-Horn Lee; Ching-Fong Chang (Fish Physiology and Biochemistry, 2005)

Detection of cefotaxime-resistant CTX-M-3 in clinical isolates ofSerratia marcescens - Mei-Fen Tsou; Wen-Liang Yu; Siu Wan Hung; Chizh-Ju Chi; Chieh-Ju; Ssu Ching Chen; Lii-Tzu Wu (Folia Microbiologica, 2004)

3-D Shear Wave Velocity Structure of the Crust and Upper Mantle in South China Sea and its Surrounding Regions by Surface Wave Dispersion Analysis - Hsin-Hung Wu; Yi-Ben Tsai; Tung-Yi Lee; Ching-Hua Lo; Chao-Hui Hsieh; Dinh Van Toan (Marine Geophysical Research, 2004)

Glutathione S-Transferase GSTM1, GSTT1 and p53 Codon 72 Polymorphisms in Human Tumor Cells - Masatsugu UEDA; Yao-Ching HUNG; Yoshito TERM; Koji KANDA; Mikio TAKEHARA; Hikari YAMASHITA; Hiroyuki YAMAGUCHI; Daisuke AKISE; Masayuki YASUDA; Koji NISHIYAMA; Minoru UEKI (Human Cell, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

ESEEM studies of succinate:ubiquinone reductase from Paracoccus denitrificans - Shao-Ching Hung; Christopher V. Grant; Jeffrey M. Peloquin; A. Reginald Waldeck; R. David Brit; Sunney I. Chan (JBIC Journal of Biological Inorganic Chemistry, 2000)

The effects of light and nitrate levels on the relationship between nitrate reductase activity and 15 NO 3 − uptake: Field observations in the East China Sea - Chin‐Chang Hung; George T. F. Wong; Kon‐Kee Liu; Shiah Fuh‐Kwo; Gong Gwo‐Ching (Limnology and Oceanography, 2000)
Nitrate reductase activity (NRA) and 15 NO 3 − uptake (NU) were determined in the East China Sea and the adjoining Kuroshio in May 1996, at six stations covering a range of hydrographic conditions: the nutrient‐rich and fresherplume of Changjiang Diluted Water along the Chinese coast, the nutrient‐rich upwelling Kuroshio Subsurface Water at the shelf edge northeast of Taiwan, the oligotrophic Kuroshio Surface Water and the mixing zones among these water masses on the shelf. The values of NRA in the surface mixed layer ranged between 16 and 0.1 nM‐N h −1 , whereas those of NU ranged between 37 and 1 nM‐N h −1 . Higher NRA and NU were found in the frontal zone between the coastal and shelf waters and in the upwelling zone, whereas the lowest values were found in the surface Kuroshio. The NRA/Chl a ratio increased linearly with increasing NU/primary production ratio in the sequence: Kuroshio, coastal plume, upwelling zone and mixing zones in the shelf. This is probably a reflection of the varying nutrient condition and the relative importance of NU in sustaining the biomass in these regions. In nitrate‐ and light‐replete waters, the average NU/NRA was 1.0 ± 0.3. NRA was linearly related to NU so that NU = 1.08 (± 0.07)NRA ( r 2 = 0.79). Thus, NRA may be used for estimating NU in these waters. In nitrate‐deficient and light‐replete waters, the average NU/NRA was 4 ± 4. These high and variable values of NU/NRA might have been caused by an over‐estimation of NU as a result of the stimulatory effect of the added 15 NO 3 − on phytoplankton growth. Thus, NRA may be a more reliable indicator of the rate of 15 NO 3 − uptake in oligotrophic waters. In nitrate‐replete and light‐deficient waters, NU did not correlate well with NRA. The average NU/NRA was 0.7 ± 0.7. These low and variable values of NU/NRA suggest a possible decoupling between NRA and NU. By using the relationship between NU and NRA in nitrate‐ and light‐replete waters and the depth‐integrated inventory of NRA in the photic zone at each station, NU in oligotrophic waters, the coastal plume, upwelling waters and shelf waters can be estimated to be 0.45, 1.55, 3.12, and 3.59 mg‐N m −2 h −1 respectively. These values fall well within the range of previously reported values in similar types of water.